THE IMPACT OF DISREGARDING FORMULAIC COMPETENCE IN DEVELOPING SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS IN INDONESIA - Sukur, Silvester Goridus (JOLLT Journal of Languages and Language Teaching, 2020)
This research aims to uncover the impact of disregarding the formulaic competence in designing electronic English textbooks for SMA students in Indonesia. This research belongs to qualitative content analysis one, conducted by using content analysis research method in Indonesia from 2018 to 2019. NVivo 12 Plus was applied to manage and analyze the data that had been stored in this qualitative research software. The data were obtained from three SMA English textbooks for SMA students nationwide as the data sources. The aforesaid textbooks are Bahasa Inggris X by Widiati, U. et al., Bahasa Inggris XI by Bashir, M.; and Bahasa Inggris XII by Widiati, U. et al., all of which were issued by the Indonesian Ministry of Education and Culture in 2017 and 2018 respectively. One of the techniques applied to achieve the trustworthiness of this study was by using Kappa statistic reliability test in NVivo 12 Plus, the result of which gained the value of reliability agreement level of data > 0.75, which means that it was in excellent category. The research result demonstrated that the three chosen SMA English textbooks lacked the topics for the students to promote their formulaic competence. The impact of this point made the students unable to learn such formulaic-competence-related materials. This case would make them find it hard to improve their communicative competence and reading comprehension skill. Therefore, it is suggested that, for the future revised edition, the writers of the textbooks for SMA students all around Indonesia develop the content of the textbooks comprehensively including the materials for formulaic competence. Keywords: textbook, formulaic competence, communicative competence